2000
DOI: 10.1002/1096-8628(20010101)98:1<25::aid-ajmg1015>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of skewed X-chromosome inactivation in 47,XXY and 48,XXYY Klinefelter patients

Abstract: Klinefelter (47,XXY) syndrome occurs in approximately 1:800 male births and accounts for about 10-20% of males attending infertility clinics. Recent studies have shown no obvious phenotypic differences between subjects in which the extra X-chromosome is of paternal or maternal origin; however, a minority of Klinefelter patients are adversely affected clinically and intellectually to an exceptional level, and the underlying basis of this phenotypic variation is not known. We hypothesize that skewed X-inactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 11 publications
(11 reference statements)
2
47
1
Order By: Relevance
“…For normal females, the XCI process randomly silences gene expression on one of two X chromosomes early in the development to equalize the dosage of X-linked genes to that of males (22). With respect to KS, a few studies have addressed the issue of XCI in somatic cells of KS patients, favoring the notion that XCI in KS follows the same pattern as in females (30,31). Here, we report the enrichment of XCI markers (H3K27me3 and macroH2A1) on an inactivated X chromosome (Xi) in all KS iPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…For normal females, the XCI process randomly silences gene expression on one of two X chromosomes early in the development to equalize the dosage of X-linked genes to that of males (22). With respect to KS, a few studies have addressed the issue of XCI in somatic cells of KS patients, favoring the notion that XCI in KS follows the same pattern as in females (30,31). Here, we report the enrichment of XCI markers (H3K27me3 and macroH2A1) on an inactivated X chromosome (Xi) in all KS iPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have reported on further molecular investigations in XXYY males. The parent-of-origin of the extra chromosomes has been evaluated in six cases, and all have identified the extra chromosomes as being paternal in origin [Rinaldi et al, 1979;Leal et al, 1994;Iitsuka et al, 2001]. It is believed that the phenotypic differences in XXYY syndrome and other SCAs likely result from gene dosage effects of genes in the pseudoautosomal regions (PAR) of the X and Y chromosomes that escape X-inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that meiosis I nondisjunction, in this case, is limited to the XY chromosome pair, probably because this bivalent is the most prone to nondisjunction in male gametogenesis. 19 No correlation was reported between the severity of the Klinefelter phenotype and origin of the extra X chromosome; 20 thus, we cannot predict the KS clinical outcome of this young boy after puberty. However, the early diagnosis of KS in this patient can be considered exceptional since most KS males are not identified until adulthood and it will be extremely helpful in order to anticipate testosterone replacement therapy if necessary.…”
Section: Concurrence Of Alport and Klinefelter Syndromes E Ars Et Almentioning
confidence: 91%